Hippocampal Memory Recovery After Acute Stress: A Behavioral, Morphological and Molecular Study - Aguayo, Felipe Ignacio; Tejos-Bravo, Macarena; Díaz-Véliz, Gabriela; Pacheco, Aníbal; García-Rojo, Gonzalo; Corrales, Wladimir; Olave, Felipe Antonio; Aliaga, Esteban; Ulloa, José L.; Avalos, Ana M.; Román-Albasini, Luciano; Rojas, Paulina S.; et al. (Frontiers in Molecular Neuroscience, 2018)
Several behavioral studies have shown that a single exposure to stress may improve or impair learning and memory processes, depending on the timing in which the stress event occurs in relation with the acquisition phase. However, to date it is unclear which are the molecular changes that occur at the synapse during the stress-induced memory modification and after a recovery period, in particular regarding hippocampal functioning. Therefore, the aim of the present study was to take a multidimensional approach to investigate behavioral, molecular and morphological changes induced by a single restraint stress exposure (2.5 h) and its recovery after 6 and 24 h. More specifically we investigated: i) performance on the hippocampal specific object-location task (OLT), ii) dendritic spine density, iii) activation of pathways related to cytoskeleton dynamics and iv) NMDA and AMPA receptor subunit levels in hippocampal synaptoneurosome fractions. After a single stress session, rats showed poor preference to explore an object placed in a novel position as assessed by OLT. Although this impairment occurred with no changes in dendritic spine density in CA1 neurons, there was increased activity of a cascade of proteins that favored actin remodeling and an increment in the NR2A subunit of the NMDA receptor. Although we detected impairment in OLT after 6 h of recovery from stress, spine density increased in secondary apical dendrites of CA1 neurons due to a rise of immature spines, in parallel with a transient rise in GluA2, but not GluA1 AMPA receptor subunits. Furthermore, we observed recovery in memory 24 h after stress exposure; event that was also accompanied by a recovery of NMDA and AMPA receptor subunits to control values. Altogether, these data indicate that acute stress produces reversible molecular and behavioral changes 24 h after stress, allowing full hippocampal-related memory. The study of these adaptive stress responses –allowing recovery of hippocampal functions- will help to unveil novel targets and make interventions in processes aimed at restoring hippocampal functioning impaired by repetitive stress exposure.